The economic and humanistic burden of patients in receipt of current available therapies for nAMD. (21st September 2018) - Jaffe, Dena H; Chan, Wing; Bezlyak, Vladimir; Skelly, Adrian
Aim: To determine the economic and humanistic burden of neovascular age-related macular degeneration (nAMD) in a cohort of patients treated with anti-VEGF in Europe and the US.Patients & methods: 79 respondents from the EU and 63 from the US with a self-reported diagnosis of nAMD and in current receipt of treatment, as reported in an international, general population survey, were compared with non-nAMD controls.Results: Anti-VEGF-treated nAMD patients in the EU had a greater utilization of healthcare resources, poorer quality of life and greater overall activity impairment versus non-nAMD controls. In the US cohort, treated nAMD patients had significantly greater resource utilization for ophthalmologist visits only.Conclusion: The burden of care associated with nAMD on EU and US healthcare systems, and on patients who are in receipt of nAMD therapy, is significant and likely to be unsustainable.